Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/jper.22-0093
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gingival keratinocyte monocyte chemoattractant protein‐1‐induced protein (MCPIP)‐1 and mucosa‐associated lymphoid tissue lymphoma translocation protein (MALT)‐1 expressions by periodontal bacteria, lipopolysaccharide, and interleukin‐1β

Abstract: Background:The aim of this study was to evaluate oral bacteria-and interleukin (IL)-1β-induced protein and mRNA expression profiles of monocyte chemoattractant protein-1-induced protein (MCPIP)-1 and mucosa-associated lymphoid tissue lymphoma translocation protein (MALT)-1 in human gingival keratinocyte monolayers and organotypic oral mucosal models. Methods: Human gingival keratinocyte (HMK) monolayers were incubated with Porphyromonas gingivalis, Fusobacterium nucleatum, P. gingivalis lipopolysaccharide (LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the context of periodontitis, however, little is known about the expression profile of MCPIP-1 and MALT-1 in the gingival tissues in relation to the extension of infection and inflammation. Our group has demonstrated that levels of MCPIP-1 and MALT-1 are regulated by periodontitis-associated bacteria in monolayers of gingival keratinocytes [17]. It was also demonstrated that MCPIP-1 is downregulated by P. gingivalis in gingival keratinocytes.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the context of periodontitis, however, little is known about the expression profile of MCPIP-1 and MALT-1 in the gingival tissues in relation to the extension of infection and inflammation. Our group has demonstrated that levels of MCPIP-1 and MALT-1 are regulated by periodontitis-associated bacteria in monolayers of gingival keratinocytes [17]. It was also demonstrated that MCPIP-1 is downregulated by P. gingivalis in gingival keratinocytes.…”
Section: Introductionmentioning
confidence: 83%
“…It was found that LPSmediated activation of inhibitor of transcription factor NF-kB kinase (IKK) complex phosphorylates MCPIP-1 rapidly and then phosphorylated MCPIP-1 undergoes ubiquitination and rapid degradation [26]. Moreover, it was demonstrated that P. gingivalis gingipain activity leads to a rapid degradation of MCPIP-1 in gingival keratinocytes, [17] which contributes the inflammophilic pathobiont formation [18]. In contrast to the observations, it was shown that lipopolysaccharide treatment increases the expression of MCPIP-1 through the activation of TLR-4 in murine macrophage cell line Raw264.7, in mouse primary bone marrow-derived macrophages, and in human monocyte-derived macrophages [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-23-dependent IL-17 is a powerful proinflammatory mediator that leads to bacterial overgrowth that causes periodontal disease [ 33 ]. Another study found that the modified MCPIP-1 and MALT-1 response and protein expression induced by periodontitis-related bacteria may be part of the pathogenesis of periodontitis [ 34 ]. A recent study found that circRNA forms a circRNA–miRNA‒mRNA network during the osteogenic differentiation of periodontal stem cells, which has the prospect of synchronous periodontal diagnosis and regeneration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%